Construction of the carbon–chalcogen (S, Se, Te) bond at the 2, 6-positions of BODIPY via Stille cross-coupling reaction. Issue 80 (16th September 2016) - Palao, E.; Slanina, T.; Klán, P.
Abstract : Novel 2-chalcogen- or 2, 6-dichalcogen-BODIPY derivatives were synthesized by a Pd-catalyzed C–heteroatom Stille cross-coupling reaction, overcoming the limitations of SN Ar. Abstract : Seven new 2-chalcogen- or 2, 6-dichalcogen- (S, Se, Te) BODIPY derivatives were synthesized in good to excellent yields (55–95%) by a Pd-catalyzed C–heteroatom Stille cross-coupling reaction, overcoming the limitations of SN Ar. The fluorophores show interesting tunable optical properties associated with the formation of a twisted intramolecular charge transfer excited state and competing intersystem crossing.